Auranofin and ICG-001 Emerge Synergistic Anti-tumor Effect on Canine Breast Cancer by Inducing Apoptosis via Mitochondrial Pathway - Lin, Zhaoyan; Lin, Zixiang; Zhao, Ying; Cheng, Nan; Zhang, Di; Lin, Jiahao; Zhang, Hong; Lin, Degui (Frontiers in Veterinary Science, 2021)
Canine Breast Cancer (CBC) is the most common spontaneous tumor in intact female dogs, especially in developing countries. The effective anti-tumor agents or therapies for the clinical treatment of CBC are still in need. Auranofin (AF) is a gold complex that has been attested by FDA for treating human rheumatism, which has been found as a great anti-tumor agent in recent years. ICG-001 is a small molecule inhibitor of Wnt/β-catenin pathway. In the present study, we demonstrated that combination of AF and ICG-001 could synergistically suppress the proliferation of CBC in vitro and in vivo. Moreover, the synergistical effect was related with apoptosis caused by mitochondrial damage and ROS production. In conclusion, combination of AF and ICG-001 could synergistically suppress the growth of CBC in vitro and in vivo by leading apoptosis via mitochondrial signaling pathway, and might provide a novel potential choice for the clinical treatment of CBC.